Payout restrictions and bank risk-shifting - Fulvia Fringuellotti; Thomas Kroen (Federal Reserve Bank of New York, 2024)
What are the effects of payout restrictions on bank risk-shifting? To answer this question, we exploit the restriction policies imposed during the Covid-crisis on US banks as a natural experiment. Using a highfrequency differences-in-differences empirical strategy, we show that, when share buybacks are banned and dividends restricted, banks' equity prices fall while their CDS spreads and bond yields decline. These results indicate that payout restrictions shift risk from debtholders into equityholders. Consistent with a risk-shifting channel, we find that these effects revert once restrictions are lifted. Moreover, banks that are ex-ante more reliant on share buybacks than dividends in their payout policies, decrease risk-taking relative to banks that are ex ante more dividends reliant, with those effects reverting when the restrictions are relaxed. These results indicate that payout and risk-taking choices are complementary and that regulatory payout restrictions endogenously affect bank risk-shifting incentives.
Keywords: G21; G28; G35; G38; 330; banking; payout restrictions; risk-shifting; prudential regulation